The relationship between UGT1A4 polymorphism and serum concentration of lamotrigine in patients with epilepsy - ONAT, FİLİZ; GÜLÇEBİ İDRİZ OĞLU, MEDİNE; GÖREN, MEHMET ZAFER; GÜLHAN, REZZAN (ELSEVIER, 2011)
Lamotrigine (LTG) which has a widespread use in epilepsy treatment as an antiepileptic agent is metabolized by UDP-glucuronosyl transferase (UGT) enzymes. In this study, single nucleotide polymorphisms, P24T and L48V, of the UGT1A4 enzyme have been investigated in a Turkish population of patients with epilepsy (n=131) by comparing serum levels of LTG of wild type and polymorphic subjects. High performance liquid chromatography (HPLC) was used to measure serum concentrations of LTG. The P24T and L48V polymorphisms of the UGT1A4 enzyme were analyzed with a matrix assisted laser desorption-time of flight (MALDI-TOF) mass spectrometry method. The frequencies of the heterozygous alleles for L48V or P24T polymorphisms were 22.4% and 3.8%, respectively. L48V polymorphism was found to decrease the serum concentration of LTG in patients on monotherapy or polytherapy. The LTG levels of non smoking monotherapy patients were 52% lower for the L48V polymorphism than for wild type alleles. Also the LTG levels were significantly lower for non smoking or smoking polymorphic alleles than for normal. The high frequency of the L48V polymorphism detected in the Turkish population indicates that LTG dose adjustments in patients with the UGT1A4 L48V polymorphic enzyme should be taken into account. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Lamotrigine; Genetic polymorphism; Glucuronidation; Pharmacogenomics; Pharmacotherapy; ANTIEPILEPTIC DRUGS; GLUCURONIDATION; PHARMACOKINETICS; PREGNANCY; POPULATION; PLASMA